IMPROVING STUDENTS’ ABILITY TO WRITE NARRATIVE TEXT BY USING GRAPHIC ORGANIZER - Resty Maya Sari; Wisma Yunita; Azwandi . (JOALL (Journal of Applied Linguistics and Literature), 2016)
This  paper  was  aimed  to  explain  whether  using  Graphic  Organizer  can improve students’ ability in writing narrative text and factors that influence the improvement  of  students’  ability  at  grade  IX  A  of  SMPN  22  Kota  Bengkulu  in  the 2012/2013 academic year. The result of this research shows that using graphic organizer has successfully improved the students’ ability in writing narrative text, the improvement was influenced by the used of interesting material chosen and teacher’s participation toward the students